PROSPEK USAHA BUDIDAYA IKAN KOMET (CARASSIUS AURATUS) DI KABUPATEN BURU: (Business Prospects of Comet Fish (Carassius Auratus) Cultivation in Buru District) - Umasugi, Samsia; Umagapi, Banri; Galela, Nadina (Uniqbu Journal of Exact Sciences, 2023)
Comet fish ( Carassius auratus ) is one type of freshwater fish that is popular among the public, especially for ornamental fish lovers. This is because comet fish have beautiful colors and interesting shapes and movements. Known to be very docile because it is easy to coexist with other types of fish when in one place, because of its nature that easily adapts to the environment. The purpose of this study was to determine the business prospects of Comet fish ( Carassius auratus ) cultivation in Namlea Village, Namlea District, Buru Regency. This research was conducted from June to July 2022 in Namlea Village, Namlea District, Buru Regency. The sampling method used in this study was the purposive sampling method (deliberately), namely 1 Comet fish cultivator who has the best Comet fish farming pond in Namlea Village. The analytical method used is Revenue Cost of Ratio (R/C), Financial Rate of Return (FRR) and Payback Period of Capital (PPC). The results of data analysis show that the R/C value is 4.72, the FRR is 7.7% and (PPC) is 0.13 years. So that the Comet fish farming business in Namlea Village, Namlea District, Buru Regency is feasible because it provides benefits to the Comet fish farming business.